The Effect of Welding Speed on the Laser Welding of AISI 430 Ferritic Stainless-AISI 1010 Low-Carbon Steel - Taskin, Mustafa; Caligulu, Ugur; Kolukisa, Sedat (Carl Hanser Verlag, 2009)
In this study, the effect of welding speed on the laser welding of AISI 430 ferritic stainless steel with AISI 1010 low-carbon steels was investigated. Laser welding experiments, were carried out under argon atmosphere, 2000 W constant welding power and 100, 200,300 cm/min welding speeds. The microstructures of the welded joints were examined by optical microscopy and SEM analysis. The tensile strength of the welded joints was measured. The result of all observations, tests and measurements indicated that the best properties were observed at the specimens welded at 100 cm/min welding speed.
Einfluss der Schweissgeschwindigkeit auf das Laserschweissen von ferritischem rostfreiem Stahl AISI 430 mit kohlenstoffarmem Stahl AIS11010